IL-15 Participates in the Pathogenesis of Polycystic Ovary Syndrome by Affecting the Activity of Granulosa Cells - Liu, Yan; Li, Zhi; Wang, Yang; Cai, Qingqing; Liu, Haiou; Xu, Congjian; Zhang, Feifei (Frontiers in Endocrinology, 2022)
Background Low-grade chronic inflammation may contribute to the pathogenesis of polycystic ovary syndrome (PCOS). Interleukin-15 (IL-15) is a proinflammatory cytokine involved in the development of chronic inflammation leading to obesity-associated metabolic syndrome. However, the concentration of IL-15 in follicular fluid of patients with PCOS has yet been evaluated. Objectives The aim of this study is to evaluate the expression level of IL-15 in both patients with PCOS and PCOS mice model and investigate the functional effect of IL-15 on ovarian granulosa cells. Methods The level of IL-15 in follicular fluid (FF) was measured using cytokine array and enzyme linked immunosorbent assay (ELISA) in two cohorts from 23 PCOS patients and 18 normo-ovulatory controls. PCOS mice model was induced by subcutaneously implanted with letrozole pellet for 21 days. The expression level of IL-15 in serum, ovarian, and subcutaneous adipose tissue in PCOS mice model was measured by ELISA, real-time polymerase chain reaction (RT-PCR), immunohistochemistry (IHC), and immunofluorescence. The effect of IL-15 on the proliferation and apoptosis of the KGN cells and mouse ovarian granulosa cells (GCs) were detected by CCK-8 assay and flow cytometry, respectively. Transcript expression of 17α-hydroxylase17,20-lyase (CYP17A1), cytochrome P450 family 19 subfamily A member 1(CYP19A1), FSH receptor (FSHR), steroidogenic acute regulatory protein (StAR), and proinflammatory cytokine were quantified using RT-PCR. The protein level and phosphorylation level of p38 MAPK and JNK are detected by Western blot. Concentration of dehydroepiandrosterone sulfate (DHEAS) and progesterone (P)were measured by ELISA. Results IL-15 expression in follicular fluid of patients with PCOS was significantly elevated compared with the control group, and similar results were observed in the ovarian and subcutaneous adipose tissue of PCOS mice models. Furthermore, the elevated FF IL-15 levels have a positive correlation with the serum testosterone levels. FSHR co-localized with IL-15 indicating that IL-15 production originate from ovarian granulose cells. IL-15 treatment inhibited proliferation and promoted apoptosis of KGN cells and mouse GCs. Moreover, IL-15 upregulated the transcription levels of CYP17A1, IL-1b and Ifng KGN cells. Similar results were observed in mouse GCs except concentration of DHEAS was higher in IL-15 treatment. IL-15 promoted p38 MAPK and JNK phosphorylation in KGN cells, treating KGN cells with p38 MAPK inhibitor SP600125 and JNK inhibitor SB203580 could reverse the effect of IL-15 on the proliferation and function of KGN cells. Conclusion The results indicate that IL-15 is involved in the pathogenesis of PCOS potentially by affecting survival, the inflammation state and steroidogenesis of granulosa cells. The practical significance of this association between IL-15 and the pathogenesis of PCOS needs further investigation.